Ocular comfort assessment in hydrogel and silicone hydrogel contact lens wearers - Mutalib H. A.,; Lim, Y. V. (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study was to determine ocular comfort level in subjects wearing hydrogel and silicone hydrogel contact lens wear for 30 days on extended wear basis. A total of forty-two contact lens wearers were recruited in this study. The comfort level of contact lens wearers was graded using Visual Analogue Scale (VAS) with scale from 0 to 100. Comfort level was graded at the first, fifteenth and thirtieth day of wearing, followed by an overall grading for each type of contact lens. The median comfort level achieved by hydrogel and silicone hydrogel was 80.00 with interquartile range of 26.25 and 21.25 respectively. No significant difference (p > 0.05) were found. Over time both types of lens wearing showed deterioration in comfort, which was also not significant (p > 0.05). Comfort level can be achieved with either hydrogel or silicone hydrogel lenses. The level of comfort is independent of lens material or oxygen transmissibility.